ПЕТРОГРАФИЯ И МИНЕРАЛОГИЯ УЛЬТРАКАЛИЕВЫХ ПОРОД ВОСТОЧНО-УРАЛЬСКОГО ПОДНЯТИЯ - Кораблев А.Г.; Кабанова Л.Я.; Анфилогов В.Н. (My University, 2000)
There is the description of the new ultrapotashic dykes on the Urals geology, petrography and composition of rocks and minerals. The ultrapotashic rocks is interpred as lamprophires which composition is approached to lamproites.
Keywords: 552.33